2006
DOI: 10.1037/0021-9010.91.6.1396
|View full text |Cite
|
Sign up to set email alerts
|

Effects of task interdependence on the relationship between helping behavior and group performance.

Abstract: The authors examine whether task interdependence moderates the relationship between the helping form of organizational citizenship behavior (OCB) and group performance. In a laboratory study, 62 groups with 3 members each completed a card-sequencing activity in which the level of task interdependence among group members was manipulated. Independent evaluators assessed helping by viewing videotapes of the groups' interactions during the sequencing activities. Performance was measured as a combined function of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
145
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(158 citation statements)
references
References 55 publications
3
145
0
2
Order By: Relevance
“…This is consistent with research conducted by Bachrach, Downloaded by [New York University] at 09:10 15 May 2015 Powell, Collins, and Richey (2006) and Nielsen, Bachrach, Sundstrom, and Halfhill (2012) that demonstrated positive relationships between OCB and group performance under high task interdependence situations and neutral to negative OCB-performance associations for task-independent groups. These results imply that OCB can amplify performance in taskinterdependent groups but diminish performance for task-independent groups due to the time cost of these behaviors.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with research conducted by Bachrach, Downloaded by [New York University] at 09:10 15 May 2015 Powell, Collins, and Richey (2006) and Nielsen, Bachrach, Sundstrom, and Halfhill (2012) that demonstrated positive relationships between OCB and group performance under high task interdependence situations and neutral to negative OCB-performance associations for task-independent groups. These results imply that OCB can amplify performance in taskinterdependent groups but diminish performance for task-independent groups due to the time cost of these behaviors.…”
Section: Discussionsupporting
confidence: 92%
“…However, others have suggested that interdependence is an important contingency condition or moderator (e.g., Bachrach, Powell, Collins, & Richey, 2006;Gully, Devine, & Whitney, 1995;Katz-Navon & Erez, 2005;Langfred, 2005; Van der Vegt, Emans, & Van de Vliert, 2001;Wageman, 1995). Given this, we also investigate whether interdependence moderates the influences of percentage of time allocated to team because of MTM and team virtuality on preparation activities.…”
Section: Moderating Influence Of Interdependencementioning
confidence: 94%
“…Meta-analytic results suggest that cohesion has a stronger positive association with group performance when task interdependence is high (Beal, Cohen, Burke, & McLendon, 2003;Gully, Devine, & Whitney, 1995), and primary studies reveal that helping contributes more favorably to performance evaluations and objective performance when task interdependence is high (Bachrach, Powell, Bendoly, & Richey, 2006;Bachrach, Powell, Collins, & Richey, 2006). Presumably, this is because cohesion and interpersonal helping facilitate coordination and task completion in interdependent groups but can distract attention away from task responsibilities in independent groups (Bachrach, Powell, Collins, & Richey, 2006). This evidence expands our knowledge of the important effects of interdependence on the type of performance that is noticed and valued in organizations.…”
Section: Task Interdependencementioning
confidence: 96%